Produktivitas Kerja pada Guru: Apakah Dipengaruhi oleh Motivasi Kerja, Disiplin, dan Lingkungan Kerja? - Wahyudi, Widi; Rizki, Ainur (Trends in Applied Sciences, Social Science, and Education, 2023)
This study aims to determine the effect of work motivation, discipline and work environment on work productivity teachers at SMK Al-Makmur. The population in this study were teachers of SMK Al-Makmur. The sample used was 31 respondents. The technique used for sampling is a non-probability sampling technique with a saturated sample technique. Data collection used the distribution of questionnaires to teachers of SMK Al-Makmur. The data analysis technique used is multiple linear regression analysis with data processing tools SPSS software version 29. The results of this study indicate that work motivation (X1) has a negative and significant effect on work productivity, while discipline (X2) has no effect on work productivity and work environment (X3) has no effect on work productivity.